Functional Identification and Structure Determination of Two Novel Prolidases from cog1228 in the Amidohydrolase Superfamily - Xiang, Dao Feng (2010)
Two uncharacterized enzymes from the amidohydrolase superfamily belonging to cog1228 were cloned, expressed and purified to homogeneity. The two proteins, Sgx9260c (gi|44242006) and Sgx9260b (gi|44479596), were derived from environmental DNA samples originating from the Sargasso Sea. The catalytic function and substrate profiles for Sgx9260c and Sgx9260b were determined using a comprehensive library of dipeptides and N-acyl derivative of L-amino acids. Sgx9260c catalyzes the hydrolysis of Gly-L-Pro, L-Ala-L-Pro and N-acyl derivatives of L-Pro. The best substrate identified to date is N-acetyl-L-Pro with a value of k(cat)/K(m) of 3 × 10(5) M(−1) s(−1). Sgx9260b catalyzes the hydrolysis of L-hydrophobic L-Pro dipeptides and N-acyl derivatives of L-Pro. The best substrate identified to date is N-propionyl-L-Pro with a value of k(cat)/K(m) of 1 × 10(5) M(−1) s(−1). Three dimensional structures of both proteins were determined by X-ray diffraction methods (PDB codes: 3MKV and 3FEQ). These proteins fold as distorted (β/α)(8)-barrels with two divalent cations in the active site. The structure of Sgx9260c was also determined as a complex with the N-methyl phosphonate derivative of L-Pro (PDB code: 3N2C). In this structure the phosphonate moiety bridges the binuclear metal center and one oxygen atom interacts with His-140. The α-carboxylate of the inhibitor interacts with Tyr-231. The proline side chain occupies a small substrate binding cavity formed by residues contributed from the loop that follows β-strand 7 within the (β/α)(8)-barrel. A total of 38 other proteins from cog1228 are predicted to have the same substrate profile based on conservation of the substrate binding residues. The structure of an evolutionarily related protein, Cc2672 from Caulobacter crecentus, was determined as a complex with the N-methyl phosphonate derivative of L-arginine (PDB code: 3MTW).